2014
DOI: 10.18632/oncotarget.2365
|View full text |Cite
|
Sign up to set email alerts
|

Splice variant transcripts of the anterior gradient 2 gene as a marker of prostate cancer

Abstract: Anterior gradient 2 (AGR2) is a gene predominantly expressed in mucus-secreting tissues or in endocrine cells. Its expression is drastically increased in tumors including prostate cancer. Here we investigated whether AGR2 transcript levels can be used as a biomarker to detect prostate cancer (PCa). Using a PCR-based approach, we could show that in addition to the wild-type (AGRwt long and short) transcripts, five other AGR2 splice variants (SV) (referred to as AGR2 SV-C, -E, -F, -G and -H) were present in canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…PSA is the most common biomarker for PCa detection and for following the course of metastatic PCa [30,31]. However, the course of PCa progression and clinical outcomes of PCa patients can differ even in patients with the same PSA level, Gleason score and pathological stage.…”
Section: Discussionmentioning
confidence: 99%
“…PSA is the most common biomarker for PCa detection and for following the course of metastatic PCa [30,31]. However, the course of PCa progression and clinical outcomes of PCa patients can differ even in patients with the same PSA level, Gleason score and pathological stage.…”
Section: Discussionmentioning
confidence: 99%
“…[136][137][138][139] Moreover, on the basis of the mass spectrometry proteome analysis, thousands of proteins encapsulated on and within vesicles are identified as biomarker candidates from urinary EVs or cell lines of PCa, [139][140][141][142][143][144][145][146] whereas the value as biomarkers is still controversial, and several types of research regenerate the previous biomarkers by the using targeted proteomics and immuno-assays. 134 Based on a proximity ligation assay, PC-derived EVs in blood has also shown to contain proteins specific to PCa, such as phosphatase 151 Donovan et al 152 Hendriks et al 153 Motamedinia et al 154 Royo et al 155 (Continues) sequencing reveals the potential values for miRNA served as diagnostic and prognostic biomarkers for PCa within serum or plasma EVs, 41,131,132,[158][159][160][161][162] such as miR-141 and miR-375 in serum, have been correlated with metastatic PCa. 159,163 Another study indicates that exosomal miR-1290 and miR-375 could be as prognostic markers in castration-resistant prostate cancer (CRPC).…”
Section: Pros Tate C An Cermentioning
confidence: 99%
“…tensin homolog gene (PTEN), survivin and other factors with decreased level compared to benign prostatic hyperplasia or health subjects 133,[147][148][149]. PC-based EVs show great value in comprehensively mapping nucleic acid changes in PCa via urine-or blood-based liquid biopsies, and it has been known that the EVs is important pool resource for circulating-free DNA (cfDNA)150 ; as such, some fac-Several mRNAs could be recognized as promising diagnostic and prognostic tools for the PCa[152][153][154][155][156] ; for instance, the transcripts of CDH3 from EVs were significantly decreased compared with benign hyperplasia 156 ; contrarily, the mRNA level of PTEN gene can only be detected in the patient of PC,147 and nevertheless, both of them are expected to be powerful for the diagnosis and monitoring of PCa. Candidate biomarkers for bladder cancer derived from EVs Candidate biomarkers for prostate cancer derived from EVs…”
mentioning
confidence: 99%
“…46, 55, and Figure 1). By crossing these barriers, prostasomes may stimulate the adaptive and separated from cells and large apoptotic bodies by differential centrifugation were found to contain splice variant transcripts of the anterior gradient 2 gene (AGR2), which had greater specificity than serum PSA as a marker for PCa (90). Other studies demonstrated the presence of both TMPRSS2:ERG and PCA3 in EV fractions from the urine of PCa patients (67,69).…”
Section: Prostasome-associated Pca Protein Markers In Bloodmentioning
confidence: 99%